Portfolio separation properties of the skew-elliptical distributions - Nils Chr. Framstad (University of Oslo, Department of Economics, 2011)
The two fund separation property of the elliptical distributions is extended to the skew-elliptical and by adding a number of funds equalling the rank of the skewness matrix. Some elements of the generalization to singular extended skew-elliptical distributions are covered.
Keywords: G11; C61; D81; D53; 330; Portfolio separation; mutual fund theorem; stochastic dominance; singular extended skew-elliptical distributions